VỀ ĐÁ VÔI TRẮNG KHU VỰC LỤC YÊN - YÊN BÁI - Phương, Nguyễn (Vietnam Journal of Earth Sciences, 2005)
White limestone in Luc Yen, Yen Bai is composed of chemical, mineral compositions and white level. This limestone is good enough for using in many different industrial fields, domestic use and being able to compete with international raw materials market. Salient characteristics of white limestone in Luc Yen area in comparison with other area are high monolithic level, the color and the glossy level of products made of the rock are favored in markets. This area needs to be prioritized in pland to exploit high quality cubic rock and produce art object for exporting.